Obesity and its associations with autonomic and cognitive functions in the general population - Battuvshin Lkhagvasuren; Zhiping P. Pang; Tsolmon Jadamba; Tetsuya Hiramoto; Keely Cheslack–Postava; George J. Musa; Christina W. Hoven; Nobuyuki Sudo (PLoS ONE, 2025)
Background Obesity poses a significant global health burden. This study aimed to investigate the prevalence of obesity in Mongolia and its associations with autonomic and cognitive functions while considering potential psychosocial risk factors. Methods This population-based, cross-sectional study included 382 participants who underwent physical examinations, completed health-related questionnaires, and participated in heart rate variability (HRV) testing for autonomic assessment and the mini-mental state examination for cognitive evaluation. Results Obesity prevalence was 28.1% (age-sex adjusted). Individuals with obesity were more likely to be older, married, have lower education, and engage in less physical activity. They exhibited autonomic imbalance, decreased autonomic nervous system activity, lower cognitive function, and sleep disturbances compared to the individuals without obesity. Body mass index, and waist circumference inversely correlated with HRV indices. Female sex, lower education, apartment living, alcohol consumption, sleep disturbances, and autonomic dysfunction emerged as significant risk factors for obesity. Independent predictors of autonomic dysfunction included systolic blood pressure, physical activity, and neck circumference, while age, education, height, sleep apnea, and autonomic dysfunction predicted cognitive decline. Furthermore, generalized linear mediation models revealed a partial mediation effect of autonomic dysfunction on the association between obesity and cognitive decline. Conclusion This study highlights a high prevalence of obesity in the general population (28.1%) and identifies distinct characteristics associated with the condition. Furthermore, our findings suggest a potential indirect effect of obesity on cognitive function, mediated by autonomic dysfunction. Further research is needed to elucidate the causal relationships and develop targeted interventions for high-risk groups (females, individuals with lower education) and promotion initiatives of healthy lifestyles (less alcohol, exercise, and sleep hygiene) to address both obesity and its associated health complications, including autonomic dysfunction.